3D hierarchical microspheres constructed by ultrathin MoS2-C nanosheets as high-performance anode material for sodium-ion batteries - Zhang, Wenlong; Zhou, Haihui; Huang, Zhongyuan; Li, Songlin; Wang, Chuqing; Li, Huanxin; Yan, Zhanheng; Hou, Teng; Kuang, Yafei (Journal of energy chemistry, 2020)
MoS2/C composites are considered to have great application potential in sodium-ion batteries (SIBs). It is a challenging and meaningful subject that developing high-performance anode materials via combining MoS2 and carbon effectively to give free rein to their advantages in sodium ion storage. In this work, a novel MoS2-C material was designed by using cellulose nanocrystals (CNCs) as low-cost and green carbon source. 3D hierarchical microspheres (200–250 nm) constructed by ultrathin MoS2-C nanosheets were synthesized by synchronizing the pre-carbonization of CNCs with the formation of MoS2 in hydrothermal reaction and subsequent pyrolysis process. It is found that the ultrathin MoS2-C nanosheets were composed of CNCs-derived short-range ordered carbon and few-layered MoS2. Benefiting from the unique structure and robust combination of MoS2 and CNCs-derived carbon, the ultrathin MoS2-C nanosheets composite was proved to have excellent cycling stability and superior rate performance in sodium-ion half-cell test and have high first reversible specific capacity of 397.9 mAh/g in full-cell test. This work provides a significant and effective pathway to prepare MoS2-C materials with excellent electrochemical performance for the application in large-scale energy storage systems. Three-dimensional MoS2-C microspheres composed of biomass cellulose nanocrystals (CNCs) derived carbon and few-layered MoS2 nanosheets were constructed, which have excellent cycling stability and superior rate performance in sodium-ion half/full batteries. [Display omitted]